Impact of temperature, humidity, dehydration, and psychological stress on salivary flow and xerostomia in young men: An observational study - Kayoko Ito; Kaname Nohno; Saori Funayama; Kouji Katsura; Noboru Kaneko; Keiko Tanaka; Makoto Inoue (PLoS ONE, 2026)
Xerostomia, or subjective oral dryness, is commonly reported and may occur with or without objectively reduced salivary secretion (hyposalivation). To assess salivary gland function, the salivary flow rate must be repeatedly measured over time under consistent conditions. However, given that temperature and humidity vary throughout the year, standardized measurement is difficult. Some reports have indicated that the unstimulated salivary flow rate is lower in summer than in winter, although no studies have evaluated this pattern in conjunction with humidity or dehydration. This longitudinal observational study aimed to determine the extent to which room temperature, relative humidity, body dehydration, and psychological stress are associated with unstimulated and stimulated salivary flow rates and xerostomia in healthy young men (n = 39). A questionnaire was administered to collect data regarding participants’ body mass index, medical history, medications, and degree of xerostomia (severe, moderate, mild, or none). Unstimulated and stimulated salivary flow rates, salivary cortisol and chromogranin A concentrations, urine specific gravity, room temperature, and relative humidity were measured. Psychological stress was assessed via measurements of salivary cortisol and chromogranin A concentrations. Urine specific gravity served as an indicator of hydration status. Factors influencing the salivary flow rate and xerostomia were analyzed using generalized estimating equations. The unstimulated salivary flow rate was significantly associated with temperature (p = 0.008), humidity (p = 0.039), urine specific gravity (p = 0.045), and chromogranin A concentration (p < 0.001); the stimulated salivary flow rate was not significantly linked to these factors. Furthermore, xerostomia was only related to chromogranin A concentration (p = 0.012). These results suggest that indoor environmental conditions and hydration status should be considered when interpreting changes in unstimulated salivary flow rate over time; subjective oral dryness (xerostomia) showed a significant association only with chromogranin A in this exploratory study.